Comparisons of Physical and Chemical Characteristics of Eggs Obtained using Hens Reared in Deep Litter and Free-Range Systems - İsmail Türker; Sezai Alkan (Journal of Agricultural Sciences)
This study was designed to compare the physical and chemical qualities of eggs obtained using hens reared in free-range and deep-litter systems. A total of 300 Lohmann Brown hens (150 for each housing system) were used. In the free-range system, 4 m2 grazing area was allocated for each hen. The hens were taken into layer house at 16 weeks of age. Hen egg production reached up to 50%, produced eggs were randomly sampled once every 4 weeks until 52 weeks of age and physical characteristics of eggs from each housing system were measured. Results revealed that there was no significant difference in egg shell color, egg weight, breaking strength, shell thickness, shape index, specific gravity, yolk color, albumen index, haugh unit, meat and blood spots of eggs from two housing systems. However, there was a significant difference in yolk index. It was determined that housing systems effected the chemical content of the egg and the eggs obtained from free-range system were significantly richer in essential amino acids, vitamin D3 and biotin.